EARLY DIAGNOSIS AND TREATMENT OF COLORECTAL CANCER (International journal of medical sciences, 2025)
Colorectal cancer (CRC) is one of the most common malignant tumors worldwide and a leading cause of cancer-related mortality. The prognosis of colorectal cancer largely depends on the stage at which the disease is diagnosed. Early detection significantly increases survival rates and allows the use of less aggressive treatment methods. This article discusses modern approaches to the early diagnosis of colorectal cancer, including screening methods and diagnostic tools, as well as current principles of treatment at early stages of the disease.